Egg White Extract Supplementation Improves Albumin and IGF-1 Levels in Malnourished Elderly Patients: A Randomized Controlled Trial - Mukmin, Sugianto; Nur Riviati; Mgs Irsan Saleh (HM Publisher, 2025)
Background: Malnutrition is a prevalent issue among the elderly, often leading to hypoalbuminemia (low albumin levels) and decreased serum Insulin-like growth factor 1 (IGF-1) levels. These conditions are associated with increased morbidity and mortality. Egg white extract (EWE) supplementation has shown promise in improving hypoalbuminemia. This study investigated the effects of EWE supplementation on serum albumin and IGF-1 levels in malnourished elderly patients. Methods: A double-blind randomized controlled trial was conducted, involving 46 malnourished elderly inpatients with hypoalbuminemia. Participants were randomly assigned to receive either EWE (30 grams daily) or a placebo for two weeks. Serum albumin and IGF-1 levels were measured before and after the intervention. Results: After two weeks, the EWE group showed a significant increase in both serum albumin and IGF-1 levels compared to the placebo group. The mean serum albumin level in the EWE group increased from 2.80 g/dL to 3.7 g/dL, while the placebo group remained unchanged. The mean serum IGF-1 level in the EWE group increased from 1.74 ng/mL to 24.74 ng/mL, while the placebo group experienced a smaller increase. There was a moderate positive correlation between changes in albumin and IGF-1 levels. Conclusion: EWE supplementation effectively improves serum albumin and IGF-1 levels in malnourished elderly patients with hypoalbuminemia. This intervention may help reduce malnutrition-related complications and improve overall health outcomes in this vulnerable population.